Implementasi linear programming metode simpleks dalam mencari keuntungan maksimum pada UMKM Es Dingin - Suvriadi Panggabean; Yesika Hutahaean; Veronika Stephanie Sitanggang (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2024)
In a Micro, Small and Medium Enterprises (MSMEs), business actors often do not know exactly how many goods must be produced and sold in order to get maximum profit. To find out the maximum profit and the number of products that must be produced, the simplex method in linear programming can be used. The simplex method is a method to find the optimal solution of a linear programming model with the principle of iteration. There is a tool to solve linear programs quickly, namely Lingo software that can be used to calculate many problems in a fast time. To implement this simplex method, the data taken by researchers is on MSMEs that produce Cold Drinks with the name Cold Ice. That way, the purpose of this study is to find out how much maximum profit is obtained after obtaining the optimum production amount of each product on Cold Ice in the Medan area.